2017
DOI: 10.3389/fpls.2017.01556
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptome Approach Toward Understanding Fruit Softening in Persimmon

Abstract: Persimmon (Diospyros kaki Thunb.), which is a climacteric fruit, softens in 3–5 weeks after harvest. However, little is known regarding the transcriptional changes that underlie persimmon ripening. In this study, high-throughput de novo RNA sequencing was performed to examine differential expression between freshly harvested (FH) and softened (ST) persimmon fruit peels. Using the Illumina HiSeq platform, we obtained 259,483,704 high quality reads and 94,856 transcripts. After the removal of redundant sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
1
7
0
1
Order By: Relevance
“…The abundance of volatile metabolites in mature and soft guava fruit (Moon et al ., 2018) may depend on the hydrolysis of starch, which protects cell membranes and maintains firmness. Starch degradation was also reported as playing a key role in fruit softening in banana (Musaceae) (Shiga et al ., 2011; Song et al ., 2019) and persimmon (Ebenaceae) (Jung et al ., 2017). The reference genome of guava reported here will facilitate studies on both ripening and softening mechanisms and support efforts to prolong the shelf life of guava fruits.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of volatile metabolites in mature and soft guava fruit (Moon et al ., 2018) may depend on the hydrolysis of starch, which protects cell membranes and maintains firmness. Starch degradation was also reported as playing a key role in fruit softening in banana (Musaceae) (Shiga et al ., 2011; Song et al ., 2019) and persimmon (Ebenaceae) (Jung et al ., 2017). The reference genome of guava reported here will facilitate studies on both ripening and softening mechanisms and support efforts to prolong the shelf life of guava fruits.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the upregulation of several ERFs in Hang fruit denotes that they positively contribute to the big fruit size. Numerous studies identified ERF genes as master regulators of the expression levels of phytohormones, cell wall modification, cell cycle, and other important structural genes involved in fruit development and ripening [65][66][67]. Decoding the networks connecting ERFs and other TFs identified in the present work to their target structural genes will highlight the most important genes to target for efficient fruit size manipulation in bottle gourd [68].…”
Section: Discussionmentioning
confidence: 89%
“…In addition, fruit ripening is related to ethylene production in climacteric fruits (Alexander and Grierson, 2002; Jung et al , 2017). Although ethylene controls the terminal development of fruits, it also controls various defence responses (Díaz et al ., 2002; Alexander and Grierson, 2002).…”
Section: Discussionmentioning
confidence: 99%